A new assembly of diiodine molecules at the 1, 3-dimethylimidazole-2-thione (Me2ImS) template: crystal structure of (Me2ImS)2·(I2)5. (15th March 2022) - Garau, Alessandra; Aragoni, M. Carla; Arca, Massimiliano; Caltagirone, Claudia; Demartin, Francesco; Isaia, Francesco; Lippolis, Vito; Pivetta, Tiziana
Abstract : The poly(I2 ) adduct [(Me2 ImS)2 ·(I2 )5 ] has been synthesised using a two-step process. The FT-Raman spectrum and MEP maps are discussed. Abstract : The new poly(I2 ) adduct [(Me2 ImS)2 ·(I2 )5 ] (Me2 ImS = 1, 3-dimethylimidazole-2-thione) has been synthesized and characterized by single crystal X-ray diffraction analysis. Units of [(Me2 ImS)2 ·(I2 )5 ] are located about a crystallographic inversion center, in which five diiodine molecules display interatomic contacts in a "head-to-tail" sequence giving a –(I2 )5 – chain interacting at each end with one Me2 ImS molecule, CCDC ; 2133501 . The S-bonding of Me2 ImS to I2 is described as a donor–acceptor interaction in which I2 acts as an acceptor through the σ*(I–I) orbital resulting in an electronic charge transfer from the thioamide moiety. The bond distances d (S–I(1)) (2.504(2) Å) and d (I(1)–I(2)) (3.133(1) Å) are indicative of a strong interaction. Based on the S–I and I–I bond distances, the calculated values of the electronic charge densities, and the Raman spectral data, it is reasonable to represent the compound as an extended polarised system: [(Me2 ImS)–I(1)] δ + ⋯I(2) δ − ⋯I(3)–I(4) δ − ⋯(I(5)–I(5) a )⋯I δ − –I⋯I δ − ⋯[I-(Me2 ImS)] δ + . The molecular electrostatic potential maps of the three adducts Me2 ImS·I2, Me2 ImS·I2 ·I2, and MeImHS·I2 (MeImHS = methimazole) have been reported to clearly identify the areas of charge increment (electron belt) and depletion (σ-hole), and thus the directionality of the noncovalent interactions.